2010
DOI: 10.1089/scd.2008.0375
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells, Colony-Forming Unit Fibroblasts, From Bone Marrow of Untreated Advanced Breast and Lung Cancer Patients Suppress Fibroblast Colony Formation From Healthy Marrow

Abstract: We have shown that bone marrow (BM) from untreated advanced lung and breast cancer patients (LCP and BCP) have a reduced number of colony-forming unit fibroblasts (CFU-Fs) or mesenchymal stem cells (MSCs). Factors that regulate the proliferation and differentiation of CFU-F are produced by the patients' BM microenvironment. We have now examined whether conditioned media (CM) from patients' CFU-F-derived stromal cells also inhibits the colony-forming efficiency (CFE) of CFU-F in primary cultures from healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Interestingly, only GM-CSF was exclusively expressed by CA-MSC cells compared with CAFs. GM-CSF has been reported previously to have elevated expression in ovarian and lung CA-MSCs compared with normal MSCs (12, 29). This makes GM-CSF an attractive therapeutic target, and understanding its role might have broader implications beyond pancreatic cancer to other cancer types where CA-MSCs have been shown to play a role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, only GM-CSF was exclusively expressed by CA-MSC cells compared with CAFs. GM-CSF has been reported previously to have elevated expression in ovarian and lung CA-MSCs compared with normal MSCs (12, 29). This makes GM-CSF an attractive therapeutic target, and understanding its role might have broader implications beyond pancreatic cancer to other cancer types where CA-MSCs have been shown to play a role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 93%
“…We next attempted to identify genes associated with the functional differences we observed between CA-MSCs and control MSCs. We first used qRT-PCR to analyze the expression of genes previously reported to have altered expression in MSCs associated with cancer, including IL8, GMCSF, FGF2, CCL5, and DKK1 (2,8,33). We found that CA-MSCs and MSCs treated with tumor-conditioned media expressed increased levels of both IL8 and GMCSF (Supplemental Figure 4).…”
Section: Isolation Of Ovarian Cancer-associated Mscsmentioning
confidence: 99%
“…During this almost unknown period, both intrinsic (genetic) and environmental (local and/or systemic) conditions interplay to outline the cell’s fate toward one of the possible lineages. Factors, such as age (22), culture condition (23), microenvironment (24), mechanical strain (25), and some pathologies (26, 27), appear to affect the intrinsic activity of MSCs.…”
Section: Mesenchymal Stem Cells or Marrow Stromal Cellsmentioning
confidence: 99%